2004
DOI: 10.1016/j.jacc.2004.03.072
|View full text |Cite
|
Sign up to set email alerts
|

Association of Elevated B-Type Natriuretic Peptide Levels With Angiographic Findings Among Patients With Unstable Angina and Non-ST-Segment Elevation Myocardial Infarction

Abstract: Among patients with UA/NSTEMI, elevated BNP levels are associated with tighter culprit stenosis, higher CTFC, and LAD involvement. These findings suggest that elevated BNP may be associated with a greater severity and extent of myocardial ischemic territory during the index event and may partly explain the association between elevated BNP and adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
62
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(76 citation statements)
references
References 25 publications
12
62
2
Order By: Relevance
“…The results were also consistent with those of Galvani et al that compared the whole spectrum of ACS as our study (13). In fact, higher BNP concentrations are associated with tighter culprit lesions, diameter stenosis, left descending artery or proximal culprit lesion location, slow flow in culprit artery and no-reflow phenomenon after PCI (19,20). All of these findings support the hypothesis that ischemia leads to altered myocardial stretch and causes active secretion of BNP (21).…”
Section: Discussionsupporting
confidence: 92%
“…The results were also consistent with those of Galvani et al that compared the whole spectrum of ACS as our study (13). In fact, higher BNP concentrations are associated with tighter culprit lesions, diameter stenosis, left descending artery or proximal culprit lesion location, slow flow in culprit artery and no-reflow phenomenon after PCI (19,20). All of these findings support the hypothesis that ischemia leads to altered myocardial stretch and causes active secretion of BNP (21).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, higher baseline levels of NT proB-NP was directly associated with age i.e. patients with NTproBNP > 258pg/ml were older (median age 68 yrs).These finding were consistent with earlier studies by Sadanandan S. et al, Morrow DA et al and Bassan R et al, who also reported that higher level of BNP was seen in older patients (10,11,12).Out of 72 cases NSTEACS was seen in 56 (77.7%) of cases and UA was seen in 16(22.3%) of cases. Both UA/NSTEACS were seen predominantly in males.…”
Section: Discussionsupporting
confidence: 90%
“…It was clear that though NT-proBNP level was higher among hypertensives, diabetics and smokers, still, the association was not significant. Similar observations were noted by Sadanandan et al (10). The patients who had NT-proBNP level more than 258 pg/ml were older, of female gender, had hypertension, had smoking history , positive Trop-T/I level .…”
Section: Discussionsupporting
confidence: 88%
“…[22][23][24][25][26] Finally, natriuretic peptide levels are proportional to the severity of underlying coronary artery disease, with higher levels associated with more extensive and severe lesions on coronary angiography, both in unstable angina and non-ST-segment elevation myocardial infarction and in stable coronary artery disease. [27][28][29][30] This association may explain the observed strong relationship between BNP and NTproBNP with short-and long-term mortality and new heart failure development in ACS.…”
Section: Prognostic Value Of Natriuretic Peptides In Stable Coronary mentioning
confidence: 91%
“…In a subanalysis of the Prevention of Events With Angiotensin-Converting Enzyme Inhibition (PEACE) trial, which evaluated the prognostic value of baseline BNP and NTproBNP levels in 3761 patients with low-risk, stable coronary artery disease and preserved left ventricular function, 21 BNP was an independent predictor of an increased risk of heart failure development, while NTproBNP was independently 8,11,15,17,19,20,29 Non-ST-elevation myocardial infarction [11][12][13][14][15]17,20,27,29,32 Acute coronary syndrome in the absence of detectable myocardial necrosis (unstable angina) 9,12,13,15,27,29,32 Uncomplicated percutaneous coronary intervention in the presence of stable intracardiac filling pressure 12,16 Stable coronary artery disease 6,[21][22][23][24][25][26][28][29][30] natriuretic peptides in ACS july . august 2008 .…”
Section: Prognostic Value Of Natriuretic Peptides In Stable Coronary mentioning
confidence: 99%